Late Pleistocene–Holocene palaeoenvironmental evolution of the Añamaza River valley (Iberian Range, NE Spain): Multidisciplinary approach on the study of carbonate fluvial systems. (12th May 2017) - Luzón, A.; Gauthier, A.; Pérez, A.; Pueyo-Anchuela, O.; Mayayo, M.J.; Muñoz, A.
Abstract: The uppermost Pleistocene and Holocene palaeoenvironmental evolution of the Añamaza river valley (Iberian Range, NE Spain) is deduced using multidisciplinary approach including stratigraphical, mineralogical, palynological, geochemical, geophysical methods and drilling. Main changes were registered in distinct subenvironments of a carbonate fluvial system, including the channelled zone and wetlands in the floodplain. Tufa barrages dominated although pools also existed. Geophysical survey and coring reveal tufa build-ups and pool facies also in the subsoil. Lower water temperature and scarce evaporation are deduced for the Pleistocene fluvial system that progressively changed through the Holocene, with more hydrologically closed areas and higher evaporation influence. A general aggrading evolution during warm stages related with increasing base level and damming due to fast carbonate precipitation, characterised the Holocene. Detrital tufa indicates erosive high-energy floods or colder stages when water level would decrease favouring erosion. 14 C and 230 Th/ 234 U dating reveal high sedimentation rates and three main discontinuities related with cold episodes: Younger Dryas, middle part of the Holocene Climate Optimum and Iron Age Epoch. During the uppermost Pleistocene tufa growth would be enhanced during warmer episodes as the Bølling/Allerød. In the Younger Dryas scarce vegetation favoured erosion of both, slopes and tufa constructions. Subsequent warmer temperatures during the first part of the Holocene favoured vegetated slopes, enhanced tufa growing (although interrupted in the middle part of the Holocene Climate Optimum), and development of wetlands with riparian vegetation in the floodplain, where either siliciclastics or detrital tufa incoming alternated with low-energy waters stages and mud settling. Progressive decline in tufa is deduced for the upper Holocene but it is not possible to determine whether this, and other palaeoenvironmental changes were related either to climate or increasing human activities. During the Roman and Medieval Warm Periods more oxidizing conditions in the wetlands and increasing erosion prevailed, probably conditioned by human activities. The pollen record shows for the Early Holocene development of Pinus forest with Betula, and expansion of deciduous Quercus, xerophilous and heliophilous grassland. Subsequent increasing moisture supported open forests with deciduous (Quercus, Ulmus, Corylus) and evergreen (Quercus ilex, Pistacia) species. From ca.4000 yrBP, a dominant deciduous Quercus forest with groves of Corylus, Ulmus, Acer, Fagus and Taxus expanded and human activities (grazing) occurred. From 1200 yrBP dry grassland expanded due to intensive land use (agropastoral activities). Almost completely deforested plateaus surround the site today with slopes covered by patchy grass with junipers groves and screeds with little soil.